Fipronil (active ingredient of acaricide frontline (R)) acting on the mice thyroid - Ferreira, Mateus [UNESP]; De Oliveira, Patricia Rosa [UNESP]; Denardi, Sandra Eloisi [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Wiley-Blackwell, 2012)
Fipronil, active ingredient of Frontline (R) acaricide, is a phenyl-pyrazolic derivative, and its efficacy in the elimination of several plagues, even in lower concentrations, has already been demonstrated; however, its effect on nontarget organisms has not been thoroughly explained. In this sense, the present study had the objective to evaluate the effects of different doses of fipronil in mice and determine its cytotoxic potential and possible compromises on nontarget organisms in artificial conditions. The results showed that animals exposed to fipronil presented significant alterations in the thyroidean tissue with evident follicular disorganization, decreased in the size of most follicles culminating with the rupture of smaller follicles and still with posterior fusion in a big and irregular follicle filled with colloid. The present study also revealed that the action of fipronil not only causes disorganization in the thyroidean tissue but alsoalters the chemical composition of the colloid itself (prehormone), modifying its proteic basis, which was confirmed by histochemical test for protein detection, making it clear that, in thyroids exposed to fipronil, the colloid was weakly positive or even negative for the presence of proteins in its constitution. Microsc. Res. Tech. 2011. (c) 2011 Wiley Periodicals, Inc.
Keywords: Pesticide; phenyl-pyrazolic; nontarget organisms; Histology; thyroidean tissue